Do the unemployed become successful entrepreneurs? A comparison between the unemployed, inactive and wage-earners - Pernilla Andersson; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2006)
In many countries unemployed people are helped to become self-employed. Self-employment, however, does not necessarily lead to success. Many leave self-employment after a short period and the economic outcome varies greatly. It is important to learn more about the economic outcome for unemployed who become self-employed. In the first part of the paper we analyse who became self-employed in the period from 1999 to 2002 of Swedish-born men aged 20 to 60 years who were either wage-earners, unemployed or inactive in 1998. We find that the unemployed, and even more the inactive, are overrepresented among those who become self-employed. In the second part of the paper we study the economic outcome of self-employment in 2002 for Swedish-born men who were either unemployed, inactive or wage-earners in 1998. Economic outcome in 2002 is measured using income from self-employment and having employees in the firm. The estimations show that those who were wage earners in 1998 have higher incomes and are also employing other people in their business to a much higher extent in 2002 than those who in 1998 were unemployed or inactive. This indicates that support to unemployed to become self-employed should be implemented with great care.
urn:nbn:de:101:1-2009031376
Keywords: 330